How to develop a sustainable telemedicine service? A Pediatric Telecardiology Service 20 years on - an exploratory study - Mélanie Raimundo Maia; Eduardo Castela; António Pires; Luís Velez Lapão (BMC, 2019)
Abstract Background Telemedicine services are promoting more access to healthcare. Portugal was an early adopter of telemedicine to overcome both its geological barriers and the shortage of healthcare professionals. The Pediatric Cardiology Service (PCS) at Coimbra University Hospital Centre (CHUC) has been using telemedicine to increase access and coverage since 1998. Their Pediatric Telecardiology Service has been daily connecting CHUC with 13 other Portuguese national hospitals, and regularly connecting with Portuguese-speaking African countries, through a teleconsultation platform. Methods This study aims at exploring the Pediatric Telecardiology Service's evolution, through a comprehensive assessment of the PCS's development, evolution and impact in public health, to better understand the critical factors for implementation and sustainability of telemedicine, in the context of healthcare services digitalization. A case study was performed, with cost-benefit, critical factors and organizational culture assessment. Finally, the Kingdon's framework helped to understand the implementation and scale-up process and the role of policy-making. Results With the total of 32,685 out-patient teleconsultations, growing steadily from 1998 to 2016, the Pediatric Telecardiology Service has reached national and international recognition, being a pioneer and an active promotor of telemedicine. This telemedicine service has saved significant resources, about 1.1 million euros for the health system (e.g. in administrative and logistic costs) and approximately 419 euros per patient (considering an average of 1777 patients per year). PCS presents a dominant "Clan" culture. The Momentum's critical factors for telemedicine service implementation enabled us to understand how barriers were overcome (e.g. political forces). Willingness, perseverance and teamwork, allied with partnership with key stakeholders, were the foundation for professionals' engagement and service networking development. Its positive results, new regulations and the increasing support from the hospital board, set up a window of opportunity to establish a sustainable telemedicine service. Conclusion The Pediatric Telecardiology Service enables real-time communication and the sharing of clinical information, overcoming many barriers (from geographical ones to shortage of healthcare professionals), improving access to specialized care both in Portugal and Africa. Motivation and teamwork, and perseverance, were key for the Pediatric Telecardiology Service to tackle the window of opportunity which created conditions for sustainability.